PENGARUH LKPD BERBASIS VIDEO PEMBELAJARAN INTERAKTIF PADA SISWA MI/SD TERHADAP KEMAMPUAN PENALARAN MATEMATIS - Fatkhul Arifin; Nafia Wafiqni; Tri Suryaningsih; Gumgum Gumelar F.R; Erry Utomo (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
The purpose of this research is to see the effect of Interactive Learning Video-Based Mathematics Learner Worksheets in an effort to improve mathematics-based reasoning skills in elementary school students. This research is quantitative using the type of one group pretest-posttest design, trying to answer how the Interactive Learning Video-Based Mathematics Learner Worksheet has a positive effect in learning mathematical reasoning of elementary school students. Data collection techniques using tests are tested with statistical tests in the form of t-tests. This study found that Interactive Learning Video-Based Mathematics Learner Worksheets positively influenced students' mathematics-based reasoning learning, indicated by the average difference between the pretest and posttest groups. The ease and flexibility of access to the Learner Worksheet system provides a wide opportunity for students to study it repeatedly when and where the student is able. Another finding, after the application of learning, students are able to perform mathematical manipulations well, provide reasons or evidence for the correctness of the solution quite well, draw conclusions from statements very well, and check the validity of an argument well. The habituation of mathematical reasoning structure will make students more accustomed and have good mathematical reasoning skills.